Uptake and metabolism of valsartan and candesartan in different plants. - Zellner, Laura (Jihočeská univerzita, 2023)
Due to the nowadays extensive pollution of the environment with pharmaceuticals and personal care products, plants are exposed to a significant concentration of xenobiotics. For this reason, a growing number of scientists is focussing on the interaction between these chemicals and plants. Likewise, the present work investigates the uptake and transformation of two blood pressure lowering drugs, namely candesartan and valsartan, in several plant species by high-performance liquid chromatography hyphenated with a drift-tube ion-mobility quadrupole time-of-flight mass spectrometer.
Uptake and metabolism of valsartan and candesartan in different plants.
Keywords: environmental analysis; plant metabolism; pharmaceuticals; sartans; drift-tube ion-mobility mass spectrometry; plant uptake; environmental analysis; plant metabolism; pharmaceuticals; sartans; drift-tube ion-mobility mass spectrometry; plant uptake